KONTRIBUSI ZAT GIZI MAKANAN JAJANAN TERHADAP ASUPAN ENERGI SEHARI DI INDONESIA (ANALISIS DATA SURVEY KONSUMSI MAKANAN INDIVIDU 2014) [FOOD AWAY FROM HOME (FAFH) CONTRIBUTION OF NUTRITION TO DAILY TOTAL ENERGY INTAKE IN INDONESIA] - yunita diana sari; Rika Rachmawati (Persagi, 2020)
The culture of consuming food away from home (FAFH) is part of a daily habit for almost all age groups and social classes including school-age children and adolescents. The benefit of consuming FAFH including food diversification from an early age to increase the nutrition quality of food consumed. The negative aspects are obtained when it’s consumed excessively that could cause excessive energy intake. Frequent consumption of FAFH is associated with a low intake of fruits and vegetables and also a low intake of micronutrients. FAFH contained high fat and saturated fat, less calcium, fiber, and iron compared with home-prepared foods. The study aimed to determine the nutrients contribution (energy, carbohydrates, fats, and proteins) of FAFH compared to the total daily energy intake. The study using secondary data analysis of the individual Food Consumption Survey 2014. The definition of FAFH is all foods and beverages produce outside the house but consumed by households, foods, and beverages that produce and consume at school/workplace and places like eatery places and vendors, etc.). The results of the study showed 86.529 respondent was consuming FAFH with the highest distribution of 53.9 percent in the urban area, 51.5 percent female, 44.3 percent in the 26-50 years age group and 24.3 percent at the top level of the economy. The contribution of nutrients from FAFH to total daily energy intake is 34.4 percent (606.9 kcal), protein 4.7 percent (20.7 g), fat 11.6 percent (23.2 g) and carbohydrates 18.6 percent (81.1 g). The ingredient of FAFH that mostly consumed are Cerealia and processed and the tubers and processed food groups.ABSTRAKBudaya jajan menjadi bagian dari keseharian pada hampir semua kelompok usia dan kelas sosial, termasuk anak usia sekolah dan golongan remaja. Makanan jajanan bermanfaat terhadap penganekaragaman makanan sejak kecil dalam rangka peningkatan mutu gizi makanan yang dikonsumsi. Aspek negatif makanan jajanan yaitu apabila dikonsumsi berlebihan dapat menyebabkan terjadinya kelebihan asupan energi. Seringnya mengkonsumsi makanan diluar rumah berkaitan dengan rendahnya asupan buah dan sayuran dan rendahnya asupan mikronutrien Kontribusi dari makanan jajanan tinggi akan lemak dan lemak jenuh serta kurang akan kalsium, serat, dan zat besi dibandingkan dengan makanan dari rumah. Tujuan penelitian untuk mengetahui kontribusi zat gizi (energi, karbohidrat, lemak dan protein) makanan jajanan terhadap total energi. Analisis lanjut data Survey Konsumsi Makanan Individu 2014. Definisi makanan jajanan adalah makanan dan minuman yang diolah di luar rumah tetapi dikonsumsi di rumah tangga, makanan dan minuman yang diolah dan dikonsumsi di sekolah/tempat kerja serta makanan dan minuman yang diolah dan dikonsumsi selain tempat yang diatas (rumah makan, pedagang kaki lima, dll). Jumlah responden yang mengonsumsi makanan jajanan sebanyak 86.529 dengan sebaran tertinggi 53,9 persen diperkotaan, 51,5 persen pada perempuan, 44,3 persen pada kelompok umur 26-58 tahun dan 24,3 persen pada tingkat ekonomi teratas. Kontribusi makanan jajanan terhadap total asupan energi sehari sebesar 34,4 persen. (606,9 kkal), protein 4,7 persen (20,7 gr), lemak 11,6 persen (23,2 gr) dan karbohidrat 18,6 persen (81,1 gr). Kelompok bahan makanan jajanan yang sering dikonsumsi adalah serealia dan olahan serta kelompok umbi-umbian dan olahan. [Penel Gizi Makan 2020, 43(1):29-40]